EDUKASI PENGGUNAAN MEDIA SOSIAL UNTUK MENINGKATKAN HIDUP SEHAT BAGI REMAJA - Mamesah, Marline Merke; Kurniawan, Afif; Goenarso, Roberto A; Rendra, Prizcatama Via; S, Reinaldo Dwiki; P, Adelia Aprilia; Alicea, Gabriella (Community Development in Health Journal, 2023)
Introduction & Aim: The development of technology has brought humans towards a world that is intangible and without boundaries. Teenager think that more active they are on social media, cooler they will be. Meanwhile, those who do not have social media are considered outdated and less sociable. Many bad things happen to teenagers in cyberspace, such as bullying, internet crimes, and accessing inappropriate content. Along with the many negative impacts of social media, the positive impacts of social media are also numerous. The purpose of this activity is to increase youth's knowledge about the positive benefits of social media for them. Method of Activity: This community service is carried out by providing education to teenager on how to increase productivity and live a healthy life through social media. Results: This activity was carried out at SMA 17 Agustus 1945 in 10thFebruary 2023. Surabaya and teenagers understand the importance of using social media properly and correctly. The initial stage of implementing this activity was preparing counseling materials and coordinating with the school. At the time of implementation, provide counseling with enthusiasm so that the enthusiasm of the participants is good. The evaluation was carried out by giving a questionnaire to measure the level of understanding of the material that had been given. Discussion: Social media is very useful for teenagers. The benefits of social media for adolescents include communication, learning development, and seeking health information.